2021
DOI: 10.1111/ans.17109
|View full text |Cite
|
Sign up to set email alerts
|

Skin tumour specimen shrinkage with excision and formalin fixationhow much and why: a prospective study and discussion of the literature

Abstract: Background: Surgical skin specimens are known to undergo significant shrinkage when excised and processed. The degree of shrinkage is important for medical care, research and third-party assessment. Studies to date have shown variable degrees of shrinkage. Most have included multiple and sometimes unspecified variables-different surgeons, varied sites, ill-defined excision patterns and/or multiple pathologies. This study tries to exclude many of these variables to try to ascertain a more accurate predictor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Anatomical site contributes to the degree of shrinkage. For lower limb skin tumors, it was showed that the pathology specimen is 28.6% smaller than the specimen marked for excision 15 . Excision and FFPE treatment can make the skin tumors shrink to various extents depending on the original liquid content in the sample 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anatomical site contributes to the degree of shrinkage. For lower limb skin tumors, it was showed that the pathology specimen is 28.6% smaller than the specimen marked for excision 15 . Excision and FFPE treatment can make the skin tumors shrink to various extents depending on the original liquid content in the sample 15 .…”
Section: Discussionmentioning
confidence: 99%
“…For lower limb skin tumors, it was showed that the pathology specimen is 28.6% smaller than the specimen marked for excision 15 . Excision and FFPE treatment can make the skin tumors shrink to various extents depending on the original liquid content in the sample 15 . However, temporal artery biopsies contract upon surgical excision but do not shrink further during formalin fixation 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the standard protocol, it also enabled the assessment of almost 10x more soft tissues on the scaffold cross-section. Moreover, the percentage of soft tissues (STPs) was only 1.5% lower than in the corresponding µCT cross-sections analyzed before the histopathological procedure, which may have resulted from the process of tissue shrinking during formalin fixation [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The FF is also reported to cause physiological shrinkage in tissues from a number of organs. 53 58 During diagnostics such changes are of significant importance, especially when reporting tumor size. Furthermore, it would be absolutely relevant to determine the extent of shrinkage in brain tissue, as well as to explore the potential consequences on the developed algorithms.…”
Section: Introductionmentioning
confidence: 99%